2021
DOI: 10.1002/smll.202104144
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Intrinsic Activity and Stability of Perovskite Cobaltite at Elevated Temperature Through Surface Stress

Abstract: SOFC/SOEC) functioning at elevated temperature, [1][2][3][4] electrochemical water splitting in aqueous solution, [5][6][7] and advanced oxidation processes for water treatment. [8] However, perovskite-based materials synthesized via the conventional solid-state reaction methods typically show large particle size due to high sintering temperature, thus resulting in poor catalytic performance.To enhance the device performance, various techniques have been developed to synthesize perovskite-based oxide catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 70 publications
(93 reference statements)
2
18
0
Order By: Relevance
“…4b, c, indicates that the distance between O 2p and Co 3d (D 3d-2p ) decreases from 3.34 for BSCF to 1.59 for BSCF + Co 3 O 4 . Report has also indicated that the decreased D 3d-2p distance predicts the low energy formation of Vo [54], which agrees with the aforementioned E vo results. Furthermore, although D 3d-2p is usually regarded as a good indicator of the catalyst activity at room temperature [57] and is not widely used for SOFCs, a recent study indicates that one mechanism for H-SOFC cathode reactions also contains the formation of *O 2 , *OOH, *O and *OH adsorbates [58], which shows some similarities to the ORR procedure at room temperature [57].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…4b, c, indicates that the distance between O 2p and Co 3d (D 3d-2p ) decreases from 3.34 for BSCF to 1.59 for BSCF + Co 3 O 4 . Report has also indicated that the decreased D 3d-2p distance predicts the low energy formation of Vo [54], which agrees with the aforementioned E vo results. Furthermore, although D 3d-2p is usually regarded as a good indicator of the catalyst activity at room temperature [57] and is not widely used for SOFCs, a recent study indicates that one mechanism for H-SOFC cathode reactions also contains the formation of *O 2 , *OOH, *O and *OH adsorbates [58], which shows some similarities to the ORR procedure at room temperature [57].…”
Section: Resultssupporting
confidence: 85%
“…4a shows the calculated configuration of the BSCF-Co 3 O 4 structure. Reports have indicated that the heterostructure could enhance the interface properties [54]. Therefore, the Vo formation energy (E vo ) at the BSCF-Co 3 O 4 interface was calculated, and the result indicates that the E vo at the BSCF-Co 3 O 4 interface is −2.98 eV, which is significantly lower than that for BSCF (−1.19 eV), suggesting that the formation of Vo is more favorable at the BSCF-Co 3 O 4 interface compared with BSCF.…”
Section: Resultsmentioning
confidence: 99%
“…The 3d 5/2 and 3d 3/2 peaks for Sr within a lattice (Sr lattice) were located at 131.7 and 133.4 eV, respectively, whereas the 3d 5/2 and 3d 3/2 peaks for an Sr non-lattice were at 133.7 and 135.4 eV. The intensity ratio and energy difference of the 3d 5/2 and 3d 3/2 peaks were set to be 1.5:1 and 1.7 eV, respectively. , Detailed fitting parameters and results are shown in Supporting Information Table S1. For the as-prepared PBSCF, the Sr non-lattice to Sr lattice ratio (Sr non-lattice/Sr lattice) was 0.728.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity ratio and energy difference of the 3d 5/2 and 3d 3/2 peaks were set to be 1.5:1 and 1.7 eV, respectively. 29,30 Detailed fitting parameters and results are shown in Supporting Information Table S1. For the as-prepared PBSCF, the Sr non-lattice to Sr lattice ratio (Sr non-lattice/Sr lattice) was 0.728.…”
Section: Resultsmentioning
confidence: 99%
“…Vo plays an essential role in oxygen-ion diffusion and oxygen reduction reaction (ORR) activity. 59–61 The improved Vo content in BTF is expected to facilitate the material's oxygen diffusion and exchange abilities. Fig.…”
mentioning
confidence: 99%